Effect of chronic antidepressant treatment on neurotransmitter-thyrotropin releasing hormone-thyrotropin interactions in the rat - Jaffer, A.(Abdulla) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1986.